2015
DOI: 10.7557/2.35.1.2942
|View full text |Cite
|
Sign up to set email alerts
|

Composition of late summer diet by semi-domesticated reindeer in different grazing conditions in northernmost Finland

Abstract: This study aims to investigate the diet composition of semi-domesticated reindeer (Rangifer tarandus tarandus) in late summer in different kinds of grazing conditions in northernmost Finland. The composition of diet by reindeer was determined on the grounds of microhistological analysis of feces samples collected in early August in different seasonal grazing areas (winter or summer/year-round grazing areas) in three reindeer management districts. Although the proportion of different plant groups varied between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…These value estimates are based on the observed differences of lichen biomass between different seasonal reindeer grazing areas (Kumpula et al, 2011 and lichen vulnerability to trampling due to the common weather conditions and their moisture content during each season. The parameter values for the importance of lichen as an energy resource outside the winter period are also presented in Table 2 and are based on the general food selection by reindeer during each season (Nieminen and Heiskari, 1989;Ophof et al, 2013;Bezard et al, 2015). Table 2 additionally shows unit costs and producer meat prices for the 20 northernmost herding districts (years 2010-2011), which are based on data from the Reindeer Herder's Association.…”
Section: Economic Modelmentioning
confidence: 99%
“…These value estimates are based on the observed differences of lichen biomass between different seasonal reindeer grazing areas (Kumpula et al, 2011 and lichen vulnerability to trampling due to the common weather conditions and their moisture content during each season. The parameter values for the importance of lichen as an energy resource outside the winter period are also presented in Table 2 and are based on the general food selection by reindeer during each season (Nieminen and Heiskari, 1989;Ophof et al, 2013;Bezard et al, 2015). Table 2 additionally shows unit costs and producer meat prices for the 20 northernmost herding districts (years 2010-2011), which are based on data from the Reindeer Herder's Association.…”
Section: Economic Modelmentioning
confidence: 99%
“…This synchronized association between lichens and mountain birch seedlings rather suggests that the importance of plant consumption and trampling outweighed that of plant competition. The reasons for our findings may derive from facts that reindeer graze on lichens in dry habitats to some extent also during summer (Bezard et al, 2015). Further, the vulnerability of lichens to increasing plant competition may vary among the lichen species (Martin St & Mallik, 2017) and be lower in dry and semi-dry habitats that usually have less developed plant cover compared with habitats with more prostate plants (Cornelissen et al, 2001;Ylänne et al, 2015).…”
Section: Synchronized Relationship Between Vegetation 'Shrubification' and Cryptogam Abundancesmentioning
confidence: 91%
“…Bryoria ssp.). During the summer, reindeer habitat selection depends not only on forage availability but also insect avoidance, resulting in that the semi‐dry and dry mountain birch forests are used especially in early and late summer (Bezard et al., 2015). The importance of reindeer grazing and browsing for the vegetation in these systems is well documented (Kumpula et al., 2011; Lempa et al., 2005; Oksanen & Virtanen, 1995; Sundqvist et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Only fresh faeces were collected (Malan et al 2012, Zweifel-Schielly et al 2012, Bezard et al 2015, Ferretti et al 2015, Ben Mimoun and Nouira 2016, García-González et al 2016) because this is important for assessing temporal diet changes (García-González et al 2016). The age of faeces was determined from smell, humidity and presence of mucus (Bezard et al 2015). Stenset et al (2016) estimated the age of the faeces on the basis of recent weather conditions in order to better assign the samples to the corresponding season.…”
Section: Faeces Collection and Storagementioning
confidence: 99%
“…Stenset et al (2016) estimated the age of the faeces on the basis of recent weather conditions in order to better assign the samples to the corresponding season. Aryal et al (2015) and Bezard et al (2015) observed and followed the animals and collected fresh samples in order to ensure that faeces belong to both sexes (Bezard et al 2015); but faeces collected without any observation most likely represent both sexes (Bezard et al 2015). On the other hand, it is impossible to separate faeces of different individuals (Malan et al 2012).…”
Section: Faeces Collection and Storagementioning
confidence: 99%